Metal-Catalyzed Site-Selective Monoacylation of Diols in Aqueous Media - Li, Yuyang; Kluger, Ronald (Synthesis, 2019)
Site-selective reactions of water-soluble biomolecules are being developed to produce efficient conversions in water and water/solvent mixtures. This review focuses on the use of designs based on bis-bidentate chelation of large metal ions by diols to be acylated by a co-chelated water-stable reagent. Topics discussed include: 1. The preparation and properties of water-stable acyl phosphate monoesters and their reactions with diol-chelated metal ions. 2. Site-selective monoaminoacylation of 3′-terminal diols of RNA and their applications in protein engineering. 3. Site-selective monoacylation of sugars with acyl phosphate monoesters associated with metal ions, including lanthanum and lead. The combination of metal ion, 1,2-diol, and acyl phosphate monoester produces site-selective reactions in aqueous media that can produce a general approach to site-selective mono-(amino)acylation in RNA and carbohydrates.1 Introduction2 Synthetic Aminoacylation of tRNA3 Activated Amino Acids in Water4 Metal Ions and Their Effects on the Reactivity of Acyl Phosphate Monoesters5 The Challenge of Site-Selective Acylation of Carbohydrates in Water6 Conclusions and Prospects
Keywords: site-selective; diol; acylation; aqueous; acyl phosphate monoesters; metal ions; chelation